Autistic clinical profiles, age at first concern, and diagnosis among children with autism spectrum disorder - Chen, Wen-Xiong; Liu, Xian; Huang, Zhifang; Guo, Cheng; Feng, Fangmei; Zhang, Yani; Gao, Yuanyuan; Zheng, Kelu; Huang, Jingyu; Yu, Jing; Wei, Wenqing; Liang, Simin (Frontiers in Psychiatry, 2023)
Background: To explore the relationship between autistic clinical profiles and age at first concern and at diagnosis among children with autism spectrum disorder. The clinical profiles included the severity of autism, cognition, adaptability, language development, and regression.The multivariate linear regression model was used to examine the association of diagnostic age and first-concern age with autistic clinical profiles, and with further stratification analysis.Results: A total of 801 autistic children were included. Language delay and regression were associated with earlier diagnostic age (language delay: